Responding to Sensorimotor Suggestions: From Endothelial Nitric Oxide to the Functional Equivalence Between Imagery and Perception. Issue 4 (2nd October 2019) - Santarcangelo, Enrica L.; Scattina, Eliana
Abstract: The reduced cerebellar gray matter (GM) volume observed in highly hypnotizable individuals (highs) is likely due to the excessive release of endothelial nitric oxide in the brain and could account for their behavioral (postural and visuomotor control) and physiological (paradoxical pain control after cerebellar anodal stimulation) characteristics. Reduced cerebellar GM can induce low inhibition of the cerebral cortex, thus stronger functional equivalence (FE) between imagery and perception and greater proneness to respond to sensorimotor suggestions. In fact, stronger FE suggested in highs by behavioral studies has been confirmed by topological data analysis of EEG signals recorded during sensorimotor and imagery tasks. The authors' hypothesis cannot be applied to obstructive suggestions likely sustained by mechanisms related to socio-cognitive factors, i.e., oxytocin availability.